Myogenic Potential of Canine Craniofacial Satellite Cells - La Rovere, Rita Maria Laura; Quattrocelli, Mattia; Pietrangelo, Tiziana; Di Filippo, Ester Sara; Maccatrozzo, Lisa; Cassano, Marco; Mascarello, Francesco; Barthélémy, Inès; Blot, Stephane; Sampaolesi, Maurilio; Fulle, Stefania (Frontiers in Aging Neuroscience, 2014)
The skeletal fibres have different embryological origin; the extraocular and jaw-closer muscles develop from prechordal mesoderm while the limb and trunk muscles from somites. These different origins characterise also the adult muscle stem cells, known as satellite cells (SCs) and responsible for the fibre growth and regeneration. The physiological properties of presomitic SCs and their epigenetics are poorly studied despite their peculiar characteristics to preserve muscle integrity during chronic muscle degeneration. Here we isolated SCs from canine somitic (SDM: vastus lateralis, rectus abdominus, gluteus superficialis, biceps femoris, psoas) and presomitic (PSDM: lateral rectus, temporalis and retractor bulbi) muscles as myogenic progenitor cells from young and old animals. In addition, SDM and PSDM satellite cells were obtained also from Golden retrievers affected by muscular dystrophy (GRMD). We characterised the lifespan, the myogenic potential and functions and oxidative stress of both somitic and presomitic SCs with the aim to reveal differences with ageing and between healthy and dystrophic animals. The different proliferation rate was consistent with higher telomerase activity in PSDM-SCs compared to SDM-SCs, although restricted at early passages. SDM-SCs express early (Pax7, MyoD) and late (MyHC, Myogenin) myogenic markers differently from PSDM-SCs resulting in a more efficient and faster cell differentiation. Taken together our results showed that PSDM-SCs elicit a stronger stem cell phenotype compared to SDM ones. Finally, myomiR expression profile reveals a unique epigenetic signature in GRMD satellite cells and miR-206, highly expressed in dystrophic SCs, seems to play a critical role in muscle degeneration. Thus, miR-206 could represent a potential target for novel therapeutic approaches.